Quantitative ethnobotanical assessment of medicinal plants in Zagatala District, Azerbaijan - JAVANSHIR ISA ISAYEV; GUNAY SALEH JAFAROVA; NILUFAR MUBARIZ SAFAROVA; ESMIRA MIRBABA HAJIYEVA (Society for Indonesian Biodiversity, 2026)
Abstract. Isayev JI, Jafarova GS, Safarova NM, Hajiyeva EM. 2026. Quantitative ethnobotanical assessment of medicinal plants in Zagatala District, Azerbaijan. Biodiversitas 27 (3): d270309. https://doi.org/10.13057/biodiv/d270309. This cross-sectional ethnobotanical study, conducted between 2023 and 2025, provides a quantitative assessment of medicinal plants traditionally used by the multi-ethnic communities of the Zagatala District in northwestern Azerbaijan. Ethnomedicinal knowledge was documented through structured and semi-structured interviews with 105 informants, recording 121 medicinal plant taxa belonging to 115 genera and 44 families. Quantitative ethnobotanical indices - including Use Value, Relative Frequency of Citation, Fidelity Level, Family Importance Value, and Informant Consensus Factor (UV, RFC, FL, FIV, and ICF) - were applied to assess cultural significance and knowledge consensus. The highest UV values were recorded for Crataegus orientalis (0.76), followed by Thymus caucasicus (0.74) and Cydonia oblonga (0.73). Species with high RFC values, such as Rosa tomentosa (RFC = 0.96), T. caucasicus (0.96), and Alcea rugosa (0.94), were the most frequently cited by informants. ICF values were high across all ailment categories (0.94-1.00), with particularly strong consensus for laxative uses (ICF = 0.98), cardiovascular disorders (0.98), and broncholytic uses (0.99). These findings document the rich ethnomedicinal heritage of the region and identify C. orientalis, T. caucasicus, and C. oblonga as culturally prominent species that merit further phytochemical and pharmacological investigation, while emphasizing the importance of preserving traditional knowledge and supporting sustainable management of local plant diversity. This study provides a quantitative baseline for future pharmacological validation, conservation planning, and sustainable management of medicinal plant resources in Azerbaijan and the wider Caucasus region.